Influence of light, temperature, and iron oxidation state on the dissolution rate of combusted iron particles in oxalic acid - Lausch, M; Ruan, Y.; Brockmann, P.; Zimina, Anna; Etzold, Bastian; Hussong, Jeanette (Results in Engineering, 2025)
It is essential to control the dissolution rate of iron oxide particles for a prospective acidic iron electrowinning process. In this study, the combined influence of temperature (40 – 80 ∘C) and short-wavelength light exposure on the dissolution rate of combusted iron particles in aqueous oxalic acid (0.45 mol/L) is experimentally investigated. The combusted iron particles were produced with various fuel-to-air equivalence ratios during combustion. Unlike previous dissolution studies on single–phase iron oxides, these particles comprise a heterogeneous mixture of iron oxides – primarily hematite and magnetite. In situ video recordings revealed the evolution of the particle size and morphology during dissolution. Increasing the temperature accelerated the reaction rate, and an additional light–induced enhancement became significant only above 40 ∘C for the duration of the experiments. This behavior differs significantly from that observed for hematite/maghemite mixed oxides and is attributed to the internal hematite and magnetite structure of the combusted iron particles. At 80 ∘C under short-wavelength light irradiation, a sudden decrease in the reaction rate was observed owing to solid ferrous oxide formation. Although the fuel-to-air ratio affected the iron oxide composition inside the particles, it did not significantly affect the dissolution rate of the combusted iron particle
Keywords: Iron oxide; Oxalic acid; Dissolution; Particle morphology; Metal fuel; Combusted iron particles; Iron electrowinning